Revisionen in den Volkswirtschaftlichen Gesamtrechnungen in Zeiten von Corona; Revisions in national accounts in times of corona - Christian Janz; Peter Kuntze; Tanja Mucha (Wirtschaftsdienst, 2022)
– This article explains the purpose, reasons and size of revisions in German national accounts. It presents the results of the revision carried out in the summer of 2022 for the past four reporting years and describes special features, including those caused by the coronavirus pandemic.
Keywords: E01; 330